Faktor PAD Memediasi Pengaruh Belanja Modal Pada Pertumbuhan Ekonomi Daerah Di Kabupaten/Kota Se-Bakorwil 1 Madiun - Wibisono, Nurharibnu; Rendah Istiqaroh, Choirum; Iswati, Retno; Mulyati, Tatik (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
This studi aims to test the influence of capital spending on economic accretion mediated by Original Local Government Revenue (PAD) in districts/cities in Bakorwil 1 Madiun in 2012 - 2022. Secondary data is realization of capital expenditure and PAD was got from the situs of DJPK. Ministry of Finance RI and regional economic growth with GRDP proxies obtained from BPS for various districts/cities in Bakorwil 1 Madiun. This category of study is quantitative and explanatory approach. The data analysis method usespath analysis. The results of the partial direct influence research show that capital spending has no positive and insignificant effect on regional economic development, capital expenditure has a significant positive impact on PAD and PAD has a significant positive impact on regional economic accretion. The indirect effect concludes that PAD mediates the influence of capital spending on regional economic development.